Two new species of Eutheiini in Taiwan (Coleoptera, Staphylinidae, Scydmaeninae) - Jałoszyński, Paweł (Zootaxa, 2024)
Five species of Eutheiini are known to occur in Taiwan, all belonging to the genus Eutheia Stephens. Two new species are described: Eutheia clepsydra sp. n., and Paraneseuthia spinipes sp. n. The discovery of the first Taiwanese species of Paraneseuthia, geographically not surprising, as several species occur in the south-western Ryukyuan islands, is highly unusual, because P. spinipes is morphologically distant from the Japanese and Russian Far Eastern group of species. This is the only known Paraneseuthia with modified profemora in males, and with dense groups of setae on the median lobe of aedeagus.